Apparatus for connection to private circuits run by certain public telecommunication operators. Specification for apparatus forconnection to digital circuits with interfaces according to CCITT G-series. Recommendations. G.703 64 kbit/s service using codirectional option Part 8-8.2, (31st October 1990) - British Standards Institution,
No abstract available